Physical, mechanical and morphological studies on bio-composite mixture of oil palm frond and kenaf bast fibers - Razak Wahab; Hashim W. Samsi; Mohd Tarmizi Mustafa; Mazlan Mohamed; Mohd Sukhairi Mat Rasat; Madihan Yusof (2016)
The physical, mechanical and morphological properties of bio-composite from a mixture of Oil Palm Fronds (OPF) and Kenaf Bast Fibers (KBF) are investigated. Urea formaldehyde resin used in cementing the mixtures together. The OPF and KBF were mixed at five different ratios. Testing for the physical and mechanical properties made by the European EN standards. Testing on the physical properties includes the density, water absorption, thickness swelling and wettability. Mechanical testing includes static bending for modulus of elasticity and modulus of rupture, besides internal bonding of the boards, revealed the enhanced values after increasing the resin content. The morphological studies were conducted using micrographʼs structures obtained by scanning electron microscope used in determining the distribution of the resin in the boards. The overall results showed that boards with 100% OPF and 50:50% (OPF:KBF) at 14% of resin content exhibited the highest properties compared to the other boards.